Moderating Role of Self-Esteem Between Perceived Organizational Support and Subjective Well-Being in Chinese Nurses: A Cross-Sectional Study - Yu, Mingli; Yang, Shihan; Qiu, Tian; Gao, Xuege; Wu, Hui (Frontiers in Psychology, 2019)
Purpose Nurses are undertaking tremendous physical and psychological pressure, which may reduce their subjective well-being (SWB). This study is aimed to identify the relationship among perceived organizational support (POS), self-esteem, and SWB, and to further explore whether self-esteem could be a moderator in the association between POS and SWB in Chinese nurses. Materials and Methods This study was conducted in Liaoning Province in China, in 2018. 606 valid questionnaires were collected. Demographic factors, job conditions, the Index of Well-Being, Survey of Perceived Organizational Support (SPOS), and Rosenberg’s Self Esteem Scale (RSES) were included in each questionnaire. The association among POS, self-esteem, and POS × self-esteem interaction with SWB were examined by hierarchical multiple regression analysis. The interaction was visualized by using simple slope analysis. Results Average score of SWB in Chinese nurses was 8.27 ± 2.64. Being married was positively related to SWB, while having longer work time per week, having night shift and dissatisfied with nurse-patient relationship were correlated with lower SWB. POS and self-esteem were important factors for SWB. Self-esteem could moderate the relationship between POS and SWB. When self-esteem was higher, POS had a greater effect on SWB. Conclusion Subjective well-being of nurses in the study was at a low level. Self-esteem could moderate the association between POS and SWB. More interventions related to POS and self-esteem will be helpful to improve SWB among nurses.